The effectiveness of filamentous bacteria Streptomyces spp in the treatment of organic pollutants (Samarra Journal of Pure and Applied Science, 2026)
This study was conducted during the period from 2022 to 2023 on soils contaminated with organic pollutants, where samples of contaminated soil were taken from different intersections of the Sharqat District, Salah al-Din Governorate, as well as the Rumana area, Qayyarah District, with the aim of isolating filamentous bacteria. Streptomyces from the sources of contaminated soils and their diagnosis for the purpose of using them later in the bioremediation of organic pollutants. Seven isolates were obtained from Streptomyces. From soils contaminated with organic pollutants and 8 isolates from contaminated garden soils, where all isolates were positive for Gram stain and produced amylase and catalase enzymes, and also possessed distinctive morphological characteristics on the surface of the culture media, as their colonies appeared in different shapes, the most common of which are chalky and circular, and there is also variation in the shapes and colors of the hyphae, and this bacteria is characterized by its ability to produce distinctive odors due to its ability to produce volatile compounds, and this bacteria is also characterized by its ability to grow slowly on the culture media. The treatment process using this type of bacteria showed high effectiveness in getting rid of organic pollutants. The chemical and physical properties of the polluted soil were examined before the treatment process. The percentage of organic matter was 6.899% before the treatment process. The percentage of electrical conductivity was 33407 micro siemens/cm, and the pH was 7.9. The percentages changed after the treatment process and under two conditions, one of which was controlled in the incubator and at a suitable temperature. The percentage of organic matter reached 3.381%. There was also a decrease in the value of electrical conductivity, which reached 4208 micro siemens/cm, and an increase in the pH value of 10.04. This indicated that the bacteria Streptomyces The organic matter was exploited, and under natural conditions there was more decomposition of pollutants as the percentage of organic matter reached 3.10%, and there was also a decrease in electrical conductivity of 4439 microsiemens/cm, and there was also an increase in the pH value, evidence that bacteria, Streptomyces, It has the ability to grow in harsh conditions and works to decompose and exploit organic pollutants and rid the environment of these pollutants.